Antibiotic stewardship in low- and middle-income countries: the same but different?. (November 2017) - Cox, J.A.; Vlieghe, E.; Mendelson, M.; Wertheim, H.; Ndegwa, L.; Villegas, M.V.; Gould, I.; Levy Hara, G.
Abstract: Background: Antibiotic resistance (ABR) is a quickly worsening problem worldwide, also in low- and middle-income countries (LMICs). Appropriate antibiotic use in humans and animals, i.e. antibiotic stewardship (ABS), is one of the cornerstones of the World Health Organization's global action plan for ABR. Many LMICs are in the process of developing stewardship programs. Aims: We highlight challenges for ABS initiatives in LMICs, give an outline of (inter)national recommendations and demonstrate examples of effective, contextualized stewardship interventions. Sources: We searched PubMed for articles on ABS interventions in humans in LMICs. Relevant websites and experts were consulted for additional sources. Content: Evidence on effective and feasible stewardship interventions in LMICs is limited, and challenges for implementation of interventions are numerous. Nevertheless, several initiatives at the international and local levels in Latin America, Africa and Asia have shown that ABS effective interventions are feasible in LMICs, although contextualization is essential. Implications: Specific guidance for setting up antimicrobial stewardship programs in LMICs should be developed. Strategic points might need to be progressively addressed in LMICs, such as (a) ensuring availability of diagnostic testing, (b) providing dedicated education in ABR both for healthcare workers and the general public, (c) creating or strengthening (inter)national agencies towards better regulations and audit on production, distribution and dispensing of drugs, (d) strengthening healthcare facilities, (e) exploring a broader synergism between policy makers, academia, professional bodies and civil society and (f) designing and studying easy and scalable ABS interventions for both hospital and community settings.